Health and welfare perception in health workers in two states of Mexico - Hernández Cornelio, Carolina; Priego Álvarez, Heberto; Ávalos García, María Isabel (HITOS DE CIENCIAS ECONÓMICO ADMINISTRATIVAS, 2023)
OBJECTIVE: To describe the health and welfare perception of health workers in two states in the Mexican Southeast. MATERIAL AND METHOD: Observational, comparative, cross-sectional study carried out in a population of 540 health workers in the states of Tabasco and Campeche. With prior informed consent, a validated health and welfare perception questionnaire was applied. The variables of interest were sociodemographic, self-concept of a healthy life, health, welfare, and activities that generate and produce health and welfare. Descriptive statistics was used in the SPSS-25 statistical program to analyze the information. RESULTS: Women with a high school education predominated in both states. The self-concept of health in Tabasco was associated with the biological and physiological dimensions (physically 44% and healthy 15%). They perceive that “to feel good,” you have to have a good relationship between mind and body, while in Campeche, health is seen as the counterpart of illness (35%), and eating well is what satisfies them the most. CONCLUSIONS: The health and welfare perceptions were different in each group. These findings shed light on the challenges, needs, and opportunities to promote a healthier, more empathetic, and sustainable environment for workers.